The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/eat.22727
|View full text |Cite
|
Sign up to set email alerts
|

The significant effects of puberty on the genetic diathesis of binge eating in girls

Abstract: Objective Recent data show significant phenotypic and genetic associations between ovarian hormones and binge eating in adulthood. Theories of hormonal risk focus on puberty and the possibility that hormone activation induces changes in genetic effects that then lead to differential risk for binge eating in post-puberty and adulthood. Although this theory is difficult to test in humans, an indirect test is to examine whether genetic influences on binge eating increase during the pubertal period in girls. Prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 32 publications
6
45
1
Order By: Relevance
“…Although this review focused on women of reproductive age, data suggest that other developmental periods (for example, puberty 4547 and menopause 120123 ) may be important for BE risk. Puberty and menopause are critical developmental periods during which dramatic increases or decreases in ovarian hormone levels can activate or de-activate the protective effects of estrogen on stress responsivity 124128 and BE 4547, 120122 . Future studies are needed to better understand the role of stress and ovarian hormone interactions on BE risk during these risky developmental hormonal milieus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this review focused on women of reproductive age, data suggest that other developmental periods (for example, puberty 4547 and menopause 120123 ) may be important for BE risk. Puberty and menopause are critical developmental periods during which dramatic increases or decreases in ovarian hormone levels can activate or de-activate the protective effects of estrogen on stress responsivity 124128 and BE 4547, 120122 . Future studies are needed to better understand the role of stress and ovarian hormone interactions on BE risk during these risky developmental hormonal milieus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that during risky hormonal milieus (for example, non-estrous or mid-luteal phases) there is differential regulation of risky or protective genes for BE in key neurobiological systems 44 . Data from twin studies indirectly support this possibility, as the heritability of eating disorder symptoms varies dramatically across the menstrual cycle 40 and other hormonal “events” (for example, puberty) 4547 , and suggest that ovarian hormone activation and de-activation are associated with changes in genetic risk. This is likely one set of moderators that contribute to hormone-BE associations, whereby associations between hormones and behavioral phenotypes vary by the presence/absence of risk/protective genes.…”
Section: Ovarian Hormones and Binge Eatingmentioning
confidence: 99%
“…Further, postnatal manipulations of gonadal steroids permanently alter feeding behavior and body weight in adults [190] , [191] . In addition, it has been reported that genetic effects on eating disorders are significantly stronger in post-pubertal girls than in pre-pubertal girls [192] , [193] , suggesting a potential effect of sex hormones (e.g. estrogens) on feeding behavior specifically during the puberty development.…”
Section: Estrogenic Actions In Developing Brainsmentioning
confidence: 99%
“…Data represent a secondary analysis of 813 female twins (n=450 families) 1 were enrolled in the study "Twin Study of Mood, Behavior, and Hormones during Puberty" (MBHP). Prior reports from the parent study have demonstrated that twins were representative of the broader population from which they were recruited (Burt & Klump, 2013;Klump et al, 2017;O'Connor et al, 2016). Racial and ethnic identity of those included in analyses were as follows: 79% Caucasian (n = 644), 9% African American (n = 73), and less than 1% Asian (n = 6) and American Indian or Alaska Native (n = 2).…”
Section: Participantsmentioning
confidence: 99%